Upaya Pemberian Terapi Relaksasi Distraksi untuk Menurunkan Nyeri Pasca Anestesi - Prayitno Prayitno; M. Hafiduddin (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2022)
Post-anesthesia pain is a common complaint experienced by patients after undergoing surgical procedures. Effective pain management is necessary to improve patient comfort and accelerate the recovery process. One non-pharmacological method that can be used is distraction relaxation therapy, which aims to divert the patient's attention from pain sensations, thereby reducing pain perception. This study aims to evaluate the effectiveness of distraction relaxation therapy in reducing post-anesthesia pain levels. The method used was a pre-test and post-test design with an intervention consisting of deep breathing techniques, relaxation music, and visualization. The results showed a significant reduction in pain levels after the application of distraction relaxation therapy. Therefore, this therapy is recommended as an adjunct method in post-anesthesia pain management to improve the quality of patient care.